Tanggung Jawab Pengedar Film Yang Diunggah Pada Aplikasi Tiktok Tanpa Izin Pemegang Hak Cipta - Merlin Magdalena Kaya; Teng Berlianty; Ronald Saija (Faculty of Law Universitas Pattimura, 2023)
At present, many film business actors easily obtain information through social media that develops among the public, especially film. This has been regulated in the Civil Code, Law No. 28 of 2014 concerning Copyright, Law No. 33 of 2009 concerning film and Law No. 19 of 2016 concerning amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions. However, there are still many people who violate and do not know about the regulations that have been made. The research method used is normative legal research method. The problem approach used is a statutory approach and a conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials. Management and analysis of legal materials are carried out with qualitative analysis techniques to answer problems. Based on this research, the perpetrators of unlicensed film dealers have fulfilled the elements of violations in the legislation, it can be concluded that the actions committed by the perpetrators of unlicensed film dealers on the Tiktok Application have committed illegal acts intentionally or unintentionally. The responsibility for the perpetrator of the movie dealer is to compensate for actions that cause harm to others.